Shifting Sediment Dynamics in the Coos Bay Estuary in Response to 150 Years of Modification. Issue 1 (18th January 2021) - Eidam, E. F.; Sutherland, D. A.; Ralston, D. K.; Conroy, T.; Dye, B.
Abstract: Estuaries worldwide have experienced modifications including channel deepening and intertidal reclamation over several centuries, resulting in altered fine sediment routing. Estuaries respond differently based on preexisting geometries, freshwater and sediment supplies, and extents and types of modification. The Coos Bay Estuary in Oregon is a relatively small estuary with complex geometry that has been extensively modified since 1865. A sediment transport model calibrated to modern conditions is used to assess the corresponding changes in sediment dynamics. Over ∼150 years, channel deepening (from ∼6.7 to 11 m), a 12% increase in area, and a 21% increase in volume have led to greater tidal amplitudes, salinity intrusion, and estuarine exchange flow. These changes have reduced current magnitudes, reduced bed stresses, and increased stratification, especially during rainy periods. Historically, fluvially derived sediment was dispersed across broad, deltaic‐style flats and through small tidal channels. Now, river water and sediments are diverted into a dredged navigation channel where an estuarine turbidity maximum (ETM) forms, with modeled concentrations >50 mg/L and measured concentrations >100 mg/L during discharge events. This "new" ETM supplies sediment to proximal embayments in the middle estuary and the shallow flats. Overall, sediment trapping during winter (and high river discharges) has increased more than two‐fold, owing to increased accommodation space, altered pathways of supply, and altered bed stresses and tidal asymmetries. In contrast to funnel‐shaped estuaries with simpler geometries and river‐channel transitions, these results highlight the importance of channel routing together with dredging in enhancing sediment retention and shifting pathways of sediment delivery. Plain Language Summary: Estuaries worldwide are commonly dredged to accommodate development. Related modifications, including dumping of dredge spoils, construction of jetties, waterfront reclamation, and so on all serve to change the geometry of estuaries. These modifications can result in changes to how water and sediment flow through the estuary. We used a high‐resolution model of water and sediment dynamics in the Coos Bay estuary in Oregon, together with modern and historic bathymetric (depth) data from the estuary, to assess how 150 years of modification (dredging and other projects) have altered the storage and transport. Overall, the model results suggest that the estuary now retains more sediment, owing largely to sediment trapping in the deepened navigation channel. This is an effect of changes in how water flows through the system and the additional space created to hold sediment (accommodation space). More nuanced changes have occurred on shallow intertidal flats and in subembayments, which have also led to increased sediment retention Key Points: Dredging and other estuarine modifications have altered hydrodynamics and sediment pathways in the Coos Bay Estuary for >150 years Rerouting of the river has caused preferential sediment routing into a dredged navigation channel, where a turbidity maximum now forms Based on modeling of historic and present conditions, the estuary now retains more sediment, in channels, flats, and embayments